Gut Microbes Reveal Pseudomonas Medicates Ingestion Preference via Protein Utilization and Cellular Homeostasis Under Feed Domestication in Freshwater Drum, Aplodinotus grunniens - Song, Changyou; Wen, Haibo; Liu, Guangxiang; Ma, Xueyan; Lv, Guohua; Wu, Ningyuan; Chen, Jianxiang; Xue, Miaomiao; Li, Hongxia; Xu, Pao (Frontiers in Microbiology, 2022)
With the strong demand for aquatic products, as well as rapid decrease of global fishery resources and capture fisheries, domesticate animals to provide more high-quality proteins is meaningful for humans. Freshwater drum (Aplodinotus grunniens) is widely distributed in the wild of North America. However, the research on A. grunniens and the feed domestication with artificial compound diets remains unclear. In this study, a 4-month feeding domestication experiment was conducted with A. grunniens larval to evaluate the underlying mechanism and molecular targets under ingestion performance alternation. From the result, the final body weight exhibited significant increase between unfavorable with the feed (WT, 5.3 g) and feed domesticated group (DOM, 114.8 g). Meanwhile, digestive capacity related enzymes activity of amylase, lipase, and trypsin were increased in DOM. Appetite and perception related gene of NPY4R, PYY, and LEPR were activated in DOM. 16s rRNA reveal Pseudomonas was increased from 58.74% to 89.77% in DOM, which accounts for the dominant up-regulated microbe in genus level, as followed by Plesiomonas. Analogously, Mycobacterium, Methylocystis, and Romboutsia were also account for the down-regulated microbes in diversity. Transcriptome and RT-PCR analysis reveal DOM significantly improved protein digestion and absorption, inhibited apoptosis by AGE-RAGE signaling, and activated extracellular matrix remodeling by Relaxin signaling. Integrated analysis between microbiome-transcriptome reveal Pseudomonas medicated ingestion capacity, protein utilization and cellular homeostasis might be the underlying mechanism under feed domestication. These results indicate Pseudomonas and its medicated key genes relating to food ingestion and digestion could serve as the molecular targets for feed domestication and sustainable development in A. grunniens.